Tribonacci and Tribonacci-Lucas Matrix Sequences with Negative Subscripts - Soykan, Yüksel (Communications in Mathematics and Applications, 2020)
In this paper, we define Tribonacci and Tribonacci-Lucas matrix sequences with negative indices and investigate their properties.